Respuesta :

Answer:

1.) 0

2.) -5

3.) 3.08

4.) 4

5.) 24.75

Hope this help!

Step-by-step explanation:

1.) 3(−1)2−(2)(−1)−5

=(3)(1)−(2)(−1)−5

=3−(2)(−1)−5

=3−(−2)−5

=5−5

=0

2.) 3(02)−(2)(0)−5

=(3)(0)−(2)(0)−5

=0−(2)(0)−5

=0−0−5

=0−5

=−5

3.)3(1.22)−(2)(1.2)−5

=(3)(1.44)−(2)(1.2)−5

=4.32−(2)(1.2)−5

=4.32−2.4−5

=1.92−5

= 3.08

4.) 3(22)−(2)(2)−5

=(3)(4)−(2)(2)−5

=12−(2)(2)−5

=12−4−5

=8−5

= 3

5.)3(3.52)−(2)(3.5)−5

=(3)(12.25)−(2)(3.5)−5

=36.75−(2)(3.5)−5

=36.75−7−5

=29.75−5

=24.75